Early evidence of stress in immortalized neurons exposed to diesel particles: the role of lipid reshaping behind oxidative stress and inflammation. (1st November 2018) - Milani, Chiara; Corsetto, Paola Antonia; Farina, Francesca; Botto, Laura; Lonati, Elena; Massimino, Luca; Rizzo, Angela Maria; Bulbarelli, Alessandra; Palestini, Paola
Highlights: HT22 cells viability was not affected by 3 h–24 h of DEP exposure. DEP treatment induced oxidative stress-related proteins increase in HT22 cells. DEP treatment promoted inflammation-related proteins increase in HT22 cells. 24 h of DEP treatment caused lipid reshaping and membrane rigidity in HT22 cells. 24 h of DEP treatment affected APP processing-related proteins in HT22 cells. Abstract: Diesel combustion is the major source of fine particle road emission, whose solid fraction is represented by diesel exhaust particles (DEP). Many studies indicate the contribution of DEP to the onset of different neurological diseases, such as Alzheimer's disease (AD), identifying oxidative stress and neuroinflammation as two cardinal processes of brain damage. This study aimed to investigate the effects of different concentrations of DEP (10 μg/ml and 50 μg/ml) on the mouse HT22 cells treated for 3 h or 24 h. Our results demonstrated that DEP contributed to an increased oxidative stress, defined by overexpression of HO-1, Hsp70 and Cyp1b1 protein levels. Moreover, an inflammatory-related processes were also observed, as COX-2 and iNOS levels were higher in treated cells when compared to the control. Furthermore, our investigations highlighted the alteration of fatty acid composition, total cholesterol content in cells and media, and of membrane fluidity, suggesting a lipid reshaping after DEP treatment. Finally, we detected APP and BACE1 increase after 24 h of treatment with 50 μg/ml of DEP. Indeed, our results propose a role of acute exposure in the onset of a deleterious mechanism for AD neurodegeneration, even though no differences were observed in p-APP Thr668 levels, BACE1 activity and APP C-terminal fragment beta amount.